A rare case report of aplasia cutis congenita of the scalp with triplet skin defects in non-syndromic newborn - Abuzarifa, Naim Sulaiman; Wan Sulaiman, Wan Azman (International Surgery Journal, 2021)
Aplasia cutis congenita is an uncommon localized or widespread congenital skin condition characterized by the absence of the skin, and occasionally underlying tissues occurs in about one every 10.000 birth mostly in the scalp as single or more than one lesion and sometimes occurs in extremities and trunk with an uncertain cause and can be associated with numerous syndromes or can be sporadic which is diagnosed clinically and usually conservatively managed but sometimes surgical intervention needed. In this literature, we present nonsyndromic newborn Malay girl normally delivered with 35 weeks gestational age with triplet skin raw areas at the vertex of the scalp with well-demarcated defect round in shape measured about 0.5 in radius covered with a noninflammatory, necrotic patch. To our knowledge, many works of literatures presented Aplasia cutis congenita at the scalp with solitary single or occasionally more than one skin defect. In contrast, in our case, we present an infrequent rare case of triplet skin defect of aplasia cutis congenita for nonsyndromic newborns.